Rapunzel syndrome causing partial gastric outlet obstruction requiring emergency laparotomy. Issue 1 (21st January 2020) - Lyons, Robert; Ismaili, Granit; Devine, Michael; Malik, Haroon
Abstract : A 16-year-old girl with a background of childhood trichophagia presented with a 2-day history of epigastric pain and associated anorexia with vomiting. An epigastric mass was palpable on examination. A CT scan revealed an intragastric trichobezoar, extending into the duodenum consistent with Rapunzel syndrome with evidence of partial gastric outlet obstruction and a possible perforation. The patient underwent an urgent laparotomy and extraction of the trichobezoar. The bezoar was removed without complication and no intraoperative evidence of perforation was detected. After an uncomplicated postoperative recovery, she was discharged home with psychiatric follow-up.